2001
DOI: 10.1081/pdt-100002248
|View full text |Cite
|
Sign up to set email alerts
|

Glass Vials for Small Volume Parenterals: Influence of Drug and Manufacturing Processes on Glass Delamination

Abstract: These results demonstrate the importance of the surface morphology created during the vial forming process. Given the diferences observed, final vial selection should include extensive microscopical and product stress testing studies on multiple vial lots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 6 publications
3
51
1
5
Order By: Relevance
“…10,11) However, the particles detected in this study mainly contained Al and P, suggesting that these particles were different from the ordinal delaminated particles reported in previous articles.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…10,11) However, the particles detected in this study mainly contained Al and P, suggesting that these particles were different from the ordinal delaminated particles reported in previous articles.…”
Section: Resultscontrasting
confidence: 53%
“…Sulfur treatment has been known to have two effects: it can restrain the alkali elution from the surface of a glass vial due to dealkalization, 27,28) but it can also pit the surface of the vial and thus enhance delamination. 10,29) Considering the fact that sulfur treatment suppressed the particle formation, dealkalization might have an effect on the suppression of particle formation. In contrast, SiO 2 coating is also known to protect the surface from alkali elution, 2,12) however, no suppression effects of the SiO 2 coating on the particle formation were shown in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15) According to numbers of research articles, the washing process is also known to enhance delamination as a result of causing pitting on the surface. 4,16) On the other hand, SiO 2 coating, a technique to coat the surface with silica, is known to be able to avoid delamination from the glass surface. 2,6) However, our previous study showed that sulfur-treated vials showed a protective effect against the Al-containing particles' formation, while otherwise the SiO 2 coating did not have any protective effects.…”
mentioning
confidence: 99%
“…Delamination, which is indicated by the presence of glass flakes, is the most well-known phenomenon and is the result of corrosive attack on the inner surface of the glass container. [4][5][6][7][8][9][10] United States Pharmacopeia (USP) ‹1660› describes factors of delamination on the surface of glass vials filled with drug solution, and also introduces tools for selecting an appropriate glass container from the point of view of avoiding delamination. 11) Among several literatures describing the propensity of forming delamination, Guadagnino has suggested that the silicon dioxide (SiO 2 ) concentration in an extract solution is an efficient indicator of glass dissolution.…”
mentioning
confidence: 99%